Corrosion behavior of FeCrAl alloy and NiCr coated Zircaloy-4 in hydrogenated water. (30th April 2022) - Jiang, Guanyu; Xu, Donghai; Wang, Yu; Liu, Lu; Guo, Shuwei; Kuang, Wenjun; Li, Yanhui
Abstract: Corrosion behavior of FeCrAl alloy and Zircaloy-4 coated with NiCr in hydrogenated water was studied. FeCrAl alloy exhibited non-uniform corrosion and increased surface roughness. Its inner oxides were mainly Fe/Cr oxides, while the outer oxides were mostly Fe spinels. NiCr coating was well-covered on the Zircaloy-4 substrate after exposure. Ni-rich spinels, Ni/Zr oxides, Fe oxides and Cr oxides were formed on the surface. Crack initiation and high porosity induced evident internal oxidation at the coating-substrate interface with the appearance of transition regions, where Ni-, Zr-, Cr- and Al-containing oxides occupied the dominance and their growth stress increased the risk of coating exfoliation. Highlights: Duplex oxides with mainly Fe spinels were formed on FeCrAl alloy. Oxides distributed dispersedly on FeCrAl and shared significant height differences. NiCr coating showed a corrosion dagame of 29.6 nm/h in depth. Oxidation occurred at interface of NiCr coating and Zircaloy-4 substrate.